POTENSI IKAN MUJAIR (Sarotherodon mossambica) SEBAGAI BIOAKUMULATOR PENCEMARAN PESTISIDA PADA LINGKUNGAN PERTANIAN - Yulvian Sani; Indraningsih Indraningsih (BERITA BIOLOGI, 2008)
An analysis of pesticide contamination in farm sites was conducted to investigate the impacts of organochlorine contamination in environmental matrices leading to pesticide residue in animal products and to identify a bioaccumulator of freshwater (mujair) fish (Sarotherodon mossambica).The observation sites were selected in accordance to the presence of animal farms within the agricultural areas applying pesticides intensively, such as Bandung, Sukabumi and Bogor districts. Samples consisting of water, soils,animal feed, freshwater fish, poultry meats, eggs and weeds were collected from these areas. The study shows that some organochlorines - OC (lindan, endosulfan and DDT metabolites) were detected from all samples. Endosulfan and lindan appeared to be used extensively for horticulture activity (corn, chilly, cassava and tobacco) in these areas, where both pesticides could also be detected either from animal products (meats and eggs) or water, freshwater fish and soils collected from the same areas.The results reveals that there were positive correlation between OC contamination in the environment and residues in animal products. The weed of babadotan (Ageratum conyzoides) was found growing abundantly around the animal farms and was able to accumulate the pesticides. Furthermore, freshwater mujair fish (S. mossambica) appeared to reduce endosulfan contaminantion in water as indicated by an increase pesticide residues in its tissues.